Effects of Selenite Ions on a Luminescence Enzymatic System - Sushko, E.S.; Zenkov, A.V.; Kudryasheva, N.S. (Karagandy University of the name of acad. E.A. Buketov, 2024)
This paper elucidates biochemical and physicochemical aspects of toxicity of a redox-active compound in organisms. Sodium selenite (Na2SeO3) was chosen as a model redox-active compound; a coupled enzymatic system from luminous marine bacteria was applied to imitate a biochemical process. We demonstrated that Na2SeO3 suppressed bioluminescence of the enzyme system; the effective inhibition concentration was 10–2 M. Besides that, Na2SeO3 decreased the content of reactive oxygen species (ROS) in aqueous solutions (enzyme- free media) at >10–3 M. Addition of enzymes and their substrates to these solutions enhanced this decrease. Correlations between dependencies of the ROS content and bioluminescence intensity on the concentration of Na2SeO3 were positive and high, confirming the ROS involvement in the bioluminescence suppression in Na2SeO3 solutions. Hence, we observed the disturbance of the native biochemical oxidative functions of dissolved oxygen derivatives under exposure to redox-active toxicants. The effects of Na2SeO3 on the bacterial enzyme system should be further compared with those on bacterial cells, which are traditionally used as a toxicity bioassay. Additionally, the use of natural microorganisms is perspective due to their ability of redox transformation of toxic selenium oxoanions to elemental selenium. This ability is important as it provides: (1) natural detoxification of water ecosystems, and (2) biosynthesis of selenium nanoparticles.
Keywords: selenite ions; ecological monitoring; toxicity mechanism; bacterial enzymatic assay; reactive oxygen species; redox processes; luminescence; enzymatic system; sodium selenite